Интеллектуальные права как ограничение права собственности - Елисеев, Виталий (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an analysis of the relation between intellectual property right system and right in rem law system. The author makes an attempt to present how the intellectual property rights limit the property rights.